2013
DOI: 10.3390/nano3030498
|View full text |Cite
|
Sign up to set email alerts
|

Conducting Polyaniline Nanowire and Its Applications in Chemiresistive Sensing

Abstract: One dimensional polyaniline nanowire is an electrically conducting polymer that can be used as an active layer for sensors whose conductivity change can be used to detect chemical or biological species. In this review, the basic properties of polyaniline nanowires including chemical structures, redox chemistry, and method of synthesis are discussed. A comprehensive literature survey on chemiresistive/conductometric sensors based on polyaniline nanowires is presented and recent developments in polyaniline nanow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
242
1
15

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 406 publications
(266 citation statements)
references
References 170 publications
(220 reference statements)
8
242
1
15
Order By: Relevance
“…Song and Choi [32] have reported that the most conductive form of PANI is the fully protonated, half-oxidized emeraldine salt form. A decrease in conductivity was observed when the polymer was deprotonated or either fully oxidized or reduced.…”
Section: Conductivity Of Graphite/pani Compositementioning
confidence: 99%
“…Song and Choi [32] have reported that the most conductive form of PANI is the fully protonated, half-oxidized emeraldine salt form. A decrease in conductivity was observed when the polymer was deprotonated or either fully oxidized or reduced.…”
Section: Conductivity Of Graphite/pani Compositementioning
confidence: 99%
“…One of them is PANI (polyaniline), which has three main distinguishable oxidation states, namely, the fully reduced (leucoemeraldine), the half oxidized (emeraldine), and the fully oxidized (pernigraniline) state, with virtually an infinite number of possible oxidation states existing in between. Protonation of the polymer, also known as doping, is the mechanism by which polyaniline becomes electrically conductive [33]. The classical chemical synthesis involves the direct oxidation of aniline monomers by chemical oxidants.…”
Section: David Publishingmentioning
confidence: 99%
“…The unprotonated and protonated forms of PANI are known as base and salt, respectively. 10 Figure 2 shows different base and salt forms of PANI in its three redox forms. Conclusively, the conductivity of PANI can be tuned by using different doping agents, varying the extent of doping, and also by controlling the chain length and morphology including the dimensions and porosity of PANI.…”
mentioning
confidence: 99%
“…The presence of two redox couples at appropriate electrochemical potential further helps PANI in facilitating the enzyme-polymer charge transfer processes, and makes it an ideal candidate to develop electrochemical biosensors. 10 Consistent and sensitive interdependence between the electrochemical response and the pH of the electrolytic solution opens new avenues to develop another set of pH sensitive electrochemical biosensors specifically for the analytes that generate either acidic or basic moieties as end products of the biochemical reaction, eg, triglycerides.…”
mentioning
confidence: 99%